Ethical and Legal Aspects of Scientific Research in Brazil - da Silva, Paulo Roberto; Barrera García, Roberto Carlos; da Silva, Rudney (Acta Bioethica, 2010)
This article has searched and analyzed the regulatory process of the ethics of scientific research in Brazil. Themethodology consisted in a systematic review, characterized by a bibliographical and documental study, results being analyzedby the content analysis technique. Legal documents studied dealt mainly with constitutional guaranties associated withscientific research, system of ethics regulation, definition of user, clinical investigations, investigations with foreign cooperation,treatment and diagnosis safeguards, human reproduction research, research with aboriginal populations, human geneticsresearch, multicenter projects and biological data bases. It can be concluded that there are protection laws for scientific researchin Brazil, establishing national priorities, determining researchers and research subjects rights and duties. There is a nationalsystem of ethics regulation established by resolutions of legislative power. Resolutions include diverse topics associated withscientific research, in line with world guidelines for research ethics, in this case the Helsinki Declaration.